ANALISIS FAKTOR PENYEBAB RENDAHNYA FOKUS BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI SEKOLAH DASAR - Anggraeni, Mutia Devi; Sutrisno, Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Focus is one of the fundamental prerequisites for meaningful learning, particularly in mathematics, a subject frequently perceived by elementary school students as abstract and difficult to grasp. This qualitative case study investigates the factors contributing to the low learning focus of second-grade students during mathematics lessons at a public elementary school. Data were obtained through in-depth interviews with the homeroom teacher and direct classroom observation, then analyzed using an interactive model of data condensation, display, and conclusion drawing. The findings reveal that students generally demonstrate high enthusiasm at the beginning of instruction, yet their attention markedly declines after approximately twenty to twenty-five minutes, particularly when the material demands deeper conceptual understanding. This decline is shaped by an interplay of internal and external factors: individual differences in mathematical comprehension, the concrete-operational characteristics of second-grade learners who still favor hands-on activity, peer distraction, and the extent to which concrete instructional media and effective classroom management are employed by the teacher. Teachers' mitigation strategies—approaching distracted students, posing direct questions, offering motivation, and involving students in manipulative-based activities—were found to partially restore attention, although they have not fully resolved the issue given its multicausal nature. These findings underscore the pedagogical importance of designing mathematics instruction that is interactive, media-supported, well-managed, and responsive to the developmental characteristics of young learners.